2018
DOI: 10.1177/2059799118769816
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative network analysis: A useful tool for investigating policy networks in transnational settings?

Abstract: The European Commission designs and promotes policy networks in almost all policy fields. Knowledge about networks is necessary for a better understanding of the overall policymaking process in multilevel governance systems like the European Union (EU). Studying EU networks helps to explain how policies emerge, how they are framed and processed, why they take the character they do, and how they might contribute to understanding the course of European integration. The political system of the EU is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…To answer the empirical questions, a qualitative network analysis (QNA) was chosen as a research strategy. Although QNA is relatively young and lacks systematic introductions and a distinctive methodology of its own, recent studies [21,35,36] suggested it as a useful technique to explore policy network-related questions from a qualitative perspective. More specifically, by employing qualitative research methods, the QNA unfolds the subjective orientations of the network actors, who have their own perceptions of whom in the network they can trust or not and why.…”
Section: Qualitative Network Analysis As a Research Strategymentioning
confidence: 99%
See 3 more Smart Citations
“…To answer the empirical questions, a qualitative network analysis (QNA) was chosen as a research strategy. Although QNA is relatively young and lacks systematic introductions and a distinctive methodology of its own, recent studies [21,35,36] suggested it as a useful technique to explore policy network-related questions from a qualitative perspective. More specifically, by employing qualitative research methods, the QNA unfolds the subjective orientations of the network actors, who have their own perceptions of whom in the network they can trust or not and why.…”
Section: Qualitative Network Analysis As a Research Strategymentioning
confidence: 99%
“…This, in contrast to quantitative SNA, allows for obtaining an "insider" instead of an "outsider" view of network relationships, which takes better into account underlying causes for the respective orientation and thus capturing the complexity and dynamics of social interaction in a policy network. To omit this "insider" view would provide a wrong image of the real structure of a policy network [21,24].…”
Section: Qualitative Network Analysis As a Research Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29] Qualitative, inductive research strategies are well suited to help address these gaps because they can help 'open up and explore complexities boxed off in quantitative work', 30 and investigate the context and understanding of the social processes that shape referral decision-making behaviours. [31][32][33] Thus qualitative research can be a very effective means to evaluate concepts that are difficult to measure quantitatively. In doing so, this research helps add depth and nuance to our understanding of referral networks.…”
Section: Introductionmentioning
confidence: 99%